PENGARUH BUDAYA ORGANISASI LINGKUNGAN KERJA TERHADAP KOMITMEN PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI GRHATAMA PUSTAKA YOGYAKARTA - Mia Aprilia; Uswatun Chasanah (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to determine the influence of organizational culture, work environment to employee commitment through job satisfaction as an intervening variable at Grhatama Pustaka Yogyakarta. The method used in this study is the quantitative method, where the data collection uses a questionnaire. The samples in this study amounted to 56 employees of Grhatama Pustaka Yogyakarta. The validity test shows that the statements in this study are valid, while the reliability test using cronbach’s alpha is stated to be reliable. The statistical analysis show that : (1) organzational culture has a positive and significant effect on employee job satisfaaction. (2) whe work environment hasn’t been proven to have an effect on employee job satisfaction. (3) job satisfaction has a positive and significant effect on employee commitment. (4) organizational culture is declared not to be related to employee commitment. (5) the work environment is stated to have no effect on employee commitment. (6) job satisfaction doesn’t significantly mediate the influence between organizational culture and employee commitment.